KORELASI ISLAM DAN PAHAM SEKULARIME - Muhammad Ridlan Fashni; Muhammad Hasbi Rosadi; Muhammad Husen Alghifari (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
Sekularism is often referred to as a doctrine that lacks adequate foundations in Islam, both in terms of structure and implementation. Over time, sekularism has caused confusion among the Muslim community. Therefore, it is important for Muslims, including intellectuals and religious leaders, to have a deep understanding of the elements of sekularism, such as its origins, teachings, and practices. This research utilizes a qualitative method, emphasizing the descriptive and interpretive analysis of verses using the thematic exegesis method. Qualitative method is a research approach that focuses on in-depth understanding and description of phenomena, in this case, the verses of the Qur'an. The thematic exegesis method, also known as thematic interpretation, means that the research centers around specific themes or topics, involving the analysis and interpretation of relevant verses related to the chosen theme.